Penerapan Pendekatan Experiential Learning untuk Meningkatkan Keterampilan Menulis Teks Narasi Kelas XII B SMAN 1 Kupang - Delima, Konstantina; Robot , Marselus; Christina, Frederika (Jurnal Lazuardi, 2024)
ABSTRACT This research aims to analyze the application of experiential learning approaches to the learning outcomes of students in Indonesian language subjects with the material of writing narrative texts. This research was carried out in XII grade Bin 1st Kupang State High School in the 2023/2024 academic year. Experiential learning approach is chosen as the primary learning approach in an effort to enhance the active involvement of pupils; Experiencial learning requires pupils to be actively involved in the learning process through practical activities and hands-on experiences. In the context of writing narrative texts, learners can directly practice writing stories based on their own experience or through simulation. Developing Creativity and Imagination; Writing narrative texts requires high imagination and creativity. This research uses a qualitative approach to the design of class action research. Data is collected through observations, interviews, and analysis of learners' learning outcomes before and after applying the experiential learning approach. The results of the study show that the application of experiential learning approaches is effective in improving the understanding of the students. In conclusion, experiential learning approach to writing narrative text materials can improve the learning outcomes of students of class XII BState High School 1 Kupang, demonstrated the presentation of I cycle accuracy of 74% increased to 91% with very good category and excellent qualification . This approach encourages active participation, deeper understanding, and development of relevant thinking skills. The recommendation for further research is to involve a wider sample and take into account other factors that may affect the learning outcome of the student. Keywords: Learning outcomes, Expereintial Learning, Writing narrative texts ABSTRAK Penelitian ini bertujuan untuk Menganalisis Penerapan pendekatan Experiential learning terhadap hasil belajar peserta didik pada mata pelajaran Bahasa indonesia dengan materi menulis teks narasi. Penelitian ini dilaksanakan di kelas XII B di SMA Negeri 1 Kupang pada tahun ajaran 2023/2024. Pendekatan Experiential learning dipilih sebagai pendekatan pembelajaran utama dalam upaya Meningkatkan keterampilan menulis, Keterlibatan Aktif Peserta Didik; Experiential learning menuntut peserta didik untuk aktif terlibat dalam proses belajar melalui kegiatan praktis dan pengalaman langsung. Dalam konteks menulis teks narasi, peserta didik bisa langsung berlatih menulis cerita berdasarkan pengalaman mereka sendiri atau melalui simulasi. Penelitian ini menggunakan pendekatan kualitatif dengan desain penelitian tindakan kelas. Data dikumpulkan melalui observasi, wawancara, dan analisis hasil belajar peserta didik sebelum dan setelah penerapan pendekatan experiential learning. Hasil penelitian menunjukkan bahwa penerapan pendekatan experiential learning efektif dalam meningkatkan pemahaman peserta didik. Hasil belajar peserta didik mengalami peningkatan yang signifikan setelah penerapan pendekatan experiential learning pada materi menulis teks narasi dengan hasil belajar peserta didik kelas XII B SMA Negeri 1 Kupang, terbukti presentase ketuntasan siklus I sebesar 74% meningkat menjadi 91% dengan kategori baik sekali dan kualifikasi tuntas (berhasil). Pendekatan ini mendorong partisipasi aktif, pemahaman yang lebih mendalam, dan pengembangan keterampilan berpikir yang relevan. Rekomendasi untuk penelitian selanjutnya adalah melibatkan sampel yang lebih luas dan memperhatikan faktor-faktor lain yang mungkin memengaruhi hasil belajar peserta didik. Kata Kunci: Hasil belajar, Expereintial Learning, Menulis teks Narasi